Numerical Simulation Analysis of Mechanical Properties on Rock Brittle–Ductility Transformation Under Different Loading Rates - Tian, Zhichao; Tang, Chunan; Yu, Chaoyun; Liu, Yejiao; Chen, Shijiang; Jin, Yun (Frontiers in Earth Science, 2022)
At present, a large number of physical tests and numerical simulations have been carried out to study the effect of confining pressure on rock deformation mechanism, and some achievements have been achieved; however, the mechanism of rock deformation in actual mine engineering needs to be further studied, for example, rock-burst is actually a unilateral unloading process of rock mass, and this process can not be completed by physical test. RFPA3D was used to simulate the brittle–ductility transformation mechanical properties of rock under different confining pressures in this paper. The damage constitutive equation of rock was derived from continuum damage mechanics; the damage coefficients of different rocks were determined based on the numerical results of stress acoustic emission, so the correctness of rock damage constitutive equation was verified. According to the derived brittle–ductility damage equation and the fitting results of ductility cumulative damage data, it was found that the development trend of rock brittleness stage was almost the same, and the extended separation occurred after entering ductility stage. The larger the Poisson’s ratio was, the longer the ductility stage was. The smaller the Poisson’s ratio was, the shorter the ductility stage was, but the larger the bearing capacity was. At the late loading stage, the ductility cumulative damage of rock showed a linear upward trend, the bearing capacity sharply decreased, the rock stability failure occurred, and the ductility damage coefficient increased gradually. The study on the brittle–ductile mechanical properties of rocks can help to deep mine’s rock-burst prediction and prevention and has significant engineering significance.